Effect of Filter Medium on Water Quality during Passive Biofilter Activation in a Recirculating Aquaculture System for Oncorhynchus mykiss - Arkadiusz Nędzarek; Małgorzata Bonisławska; Agnieszka Tórz; Adam Tański; Krzysztof Formicki (Energies, 2022)
High-performance biofilters for water purification in recirculating aquaculture systems (RAS) ensure the safety of cultures of highly nutritious fish. As the most critical step in the functioning of biofilters is their activation, the objective of this study was to evaluate the suitability of commercial artificial media, namely RK Plast (BR-1), Mutag-BioChip30 (BR-2), and LevaPor (BR-3), for the passive activation of biofilters used in rainbow trout farming. Changes in NH4+-N, NO2−-N, NO3− -N, phosphorus, and carbon concentrations were analyzed. In the first period, an increase in NH4+-N concentration was recorded, before an increase in NO2−-N concentration (maximum concentrations ranged 0.728–1.290 and 0.982–5.198 mg N dm−3, respectively), followed by a reduction and stabilization to a level safe for the fish (both below 0.100 mg N dm−3). Concurrently, a steady increase in NO3−-N concentration was noted, with a maximum concentration between 6.521 and 7.326 mg N dm−3. Total phosphorus and total carbon ranged from 0.423 to 0.548 mg P dm−3, and from 43.8 to 45.2 mg C dm−3. The study confirmed the feasibility of using the tested artificial biofilter media for rainbow trout farming in RAS with passive biofilter activation. Biofilter activation efficiency was highest for the media with the highest specific surface area (BR-2 and BR-3). The removal of ammonium nitrogen and nitrite nitrogen was above 90%. Nitrogen biotransformation was not limited by phosphorus or carbon concentrations.